George Clymer papers - Clymer, George, 1739-1813.
Holograph request (1782 January 2) from Clymer for payment for service as delegate to the U.S. Continental Congress and on reverse of request, receipts (1781 March 26 and 1782 January 30) and pay order (1782 January 7); ALS (1790 July 16) and typewritten transcript of the letter from Clymer to his son, Harry, concerning issues raised before the U.S. House of Representatives; ALS (1793 March 27; Philadelphia, Pa.) from Clymer to Edward Hand concerning the whiskey tax rebellion in Pennsylvania; and certificate (1790s) signed by Clymer, supervisor of revenue, District of Pennsylvania.
Delegate to the U.S. Continental Congress, U.S. representative, and businessman from Pennsylvania.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Clymer, Harry -- Correspondence; Hand, Edward, -- 1744-1802 -- Correspondence; Taxation -- Pennsylvania; Whiskey Rebellion, Pa., 1794.; Pennsylvania -- History -- 1775-1865.; United States -- Politics and government -- 1775-1783.; United States -- Politics and government -- 1783-1809.; Businessmen; Delegates, U.S. Continental Congress -- Pennsylvania; Representatives, U.S. Congress -- Pennsylvania